A comprehensive approach to API RP 752 and 753 building siting studies. (November 2016) - Marx, Jeffrey D.; Ishii, Benjamin R.
Abstract: Facility siting studies are an important part of process safety, and are required for facilities that fall under OSHA's PSM program. Facility siting is frequently interpreted as performing a building siting study which adheres to the guidance given in API RP 752. Building siting may also consider siting of temporary or portable buildings based on the guidance in API RP 753. While both API RP 752 and API RP 753 provide a framework and some guidance for performing building siting studies, they do not provide detailed methodologies or provide guidance on performing a detailed analysis. As a result many building siting studies are inconsistent in their overall approach, or in the way they address hazards. Due to the recent scrutiny applied to building siting studies, more attention has been given to provide evaluations which correctly describe the range of hazards that may affect an occupied building at a petrochemical facility. This paper outlines a comprehensive methodology for performing building siting studies at such facilities. The methodology addresses the applicable hazards and the available tools by which the potential impacts to building occupants can be evaluated. Highlights: Comprehensive methodology for occupied building siting evaluations. Four-stage process of evaluation. Hazard impacts and building mitigations are considered. Suggested tool set for consequence based methods and risk-based methods. Guidance for end-of-analysis criteria provided.